Pengaruh Implementasi Kebijakan Terhadap Efektivitas Pengembangan Pantai Binasi Kabupaten Tapanuli Tengah - Sianturi, Putra Felix Pradana; Sinaga, Rudi Salam (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2025)
This study evaluates the influence of policy implementation on the effectiveness of Binasi Beach development in Central Tapanuli Regency. Edward III's policy implementation model is used as an analytical framework with four main indicators: communication, resources, disposition, and bureaucratic structure. This study uses a quantitative method with a correlation technique, where data is collected through questionnaires and documentation involving Tourism Office employees, business actors, and tourists. Data analysis was carried out using Pearson Product Moment correlation test and simple linear regression. The results of the study show that the implementation of policies has not been optimal in supporting the development of Binasi Beach. The main obstacles include weak coordination, budget limitations, lack of community participation, and challenges in environmental management. Although the number of tourists increased from 10,000 in 2020 to 30,000 in 2023, this growth has not had a significant impact on the local economy. Therefore, the suggested strategies include strengthening coordination between stakeholders, improving infrastructure, optimizing digital marketing, empowering the community, and better managing the environment. With more effective policies, Binasi Beach can develop into a sustainable leading tourist destination.